Experimental Study On The Solvent-Free, Non-Catalytic Synthesis Of Ethyl Acetate By The Esterification Of Ethanol With Acetic Anhydride In A Coiled Flow Inverter - Ooi, Qian Hui (Universiti Sains Malaysia, 2022)
The elimination of solvents and catalysts pose several major challenges, such as a slow rate of reaction, low yield of main product, and an excessive production of side products. Thus, this experimental study focuses on the non-catalytic, solvent-free esterification using ethanol and acetic anhydride in a coiled flow inverter (CFI). The application of CFI, which embodies the principles of process intensification, has demonstrated great potential in narrowing the residence time distribution due to superb heat and mass transfer properties and mixing properties. Besides, the non-reversible esterification reaction between acetic anhydride and ethanol to prevent the products from shifting back to the left-hand side of the equilibrium to form the reactants. Two parameters were selected in this study, which were operating temperature (manipulated between 40 to 80 ℃) and the number of bends of the CFI (3,7, 11). The interaction between the two parameters were also analysed using Design Expert V.13 to find the optimum operating conditions. Based on the findings obtained, the optimum operating condition is at 60 ℃ using a 3-bend CFI, because under the operating conditions mentioned, the concentration of ethyl acetate, which is the main product, is the highest (1.7592 mol/ dm3), and the concentrations of acetic anhydride is low (0.8511 mol/dm3) , implying that most of the limiting reactant, which is acetic anhydride, is spent on forming the main product, ethyl acetate.